PRINCIPLES OF SOCIAL RESPONSIBILITY IN VOLUNTEER ACTIVITIES WITH Z INTERNALLY DISPLACED PERSONS - PETRYSHYN, Lyudmila (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2023)
Abstract. The article analyzes the importance of applying the principles of social responsibility in volunteer work with internally displaced persons (IDPs) in Ukraine. The relevance of the research is determined by the fact that in the context of modern social changes and social policy, the role of volunteering is characterized by the presence of such qualities as the scale of influence, universality, purposefulness, pragmatism; this determines the ability of volunteer activity to influence almost all spheres of social life and that is why it should be socially responsible to the fullest extent. The analysis of the researched problem of social responsibility is determined by the fact that the problem of volunteering in relation to IDPs is particularly significant for Ukraine in connection with the steady trend towards an increase in the share of internally displaced persons in the general structure of the population. It has been established that the problem of social responsibility in the work of volunteers acquires a socio-legal orientation if its solution violates the interests of large and small social groups, as well as institutions of state power. In the field of social tasks, which more than others are oriented towards the ideals of a social legal state, the following are effectively solved by volunteers: assistance to internally displaced persons, war veterans, participants in combat operations in the ATO / OOS, provision of social and legal assistance, assistance in the provision of communal services, improvement of territories, educational services, organization of preschool education, health care, creation of conditions for cultural and household services of the population. It is noted that socially responsible behavior has become an imperative of the state today, that is why it is necessary to act in the legal field and be regulated by certain values on which the socially responsible behavior of volunteers in working with internally displaced persons should be based. We will single out the fundamental values of social responsibility: customer orientation, teamwork, innovation and perspective orientation, professionalism and cooperation, respect, honesty, tolerance for the customer, quality and sustainability of work, preservation of the health and safety of the customer. It was established that the specified values ensure the creation of a positive atmosphere and the selection and implementation of the right solutions that provide positive long-term results for clients (IPOs) and ensure the implementation of the principles of social responsibility. Conclusions were made that volunteering is an important component of a democratic society and must necessarily be guided by the basic principles of social responsibility in volunteer, social, community service activities with all categories of clients, and in particular with internally displaced persons in Ukraine.